Comparative risk of renal, cardiovascular, and mortality outcomes in controlled, uncontrolled resistant, and nonresistant hypertension - Sim, John J.; Bhandari, Simran K.; Shi, Jiaxiao; Reynolds, Kristi; Calhoun, David A.; Kalantar-Zadeh, Kamyar; Jacobsen, Steven J. (Kidney international, 2015)
We sought to compare the risk of end-stage renal disease (ESRD), ischemic heart event (IHE), congestive heart failure (CHF), cerebrovascular accident (CVA), and all-cause mortality among 470,386 individuals with resistant and nonresistant hypertension (non-RH). Resistant hypertension (60,327 individuals) was subcategorized into two groups: 23,104 patients with cRH (controlled on four or more medicines) and 37,223 patients with uRH (uncontrolled on three or more medicines) in a 5-year retrospective cohort study. Cox proportional hazard modeling was used to estimate hazard ratios adjusting for age, gender, race, body mass index, chronic kidney disease (CKD), and comorbidities. Resistant hypertension (cRH and uRH), compared with non-RH, had multivariable adjusted hazard ratios (95% confidence intervals) of 1.32 (1.27–1.37), 1.24 (1.20–1.28), 1.46 (1.40–1.52), 1.14 (1.10–1.19), and 1.06 (1.03–1.08) for ESRD, IHE, CHF, CVA, and mortality, respectively. Comparison of uRH with cRH had hazard ratios of 1.25 (1.18–1.33), 1.04 (0.99–1.10), 0.94 (0.89–1.01), 1.23 (1.14–1.31), and 1.01 (0.97–1.05) for ESRD, IHE, CHF, CVA, and mortality, respectively. Men and Hispanics had a greater risk for ESRD within all three cohorts. Individuals with resistant hypertension had a greater risk for ESRD, IHE, CHF, CVA, and mortality. The risk of ESRD and CVA were 25% and 23% greater, respectively, in uRH compared with cRH, supporting the linkage between blood pressure and both outcomes.